Chemically tailored molecular surface modifiers for efficient and stable perovskite photovoltaics. (26th March 2021) - Liu, Yuhang; Dong, Bitao; Hagfeldt, Anders; Luo, Jingshan; Graetzel, Michael
Abstract: Perovskite solar cells (PSCs) have attracted intense attention based on their high power conversion efficiency and low production cost. However, due to the polycrystalline nature and the intrinsic hydrophilicity of the metal halide perovskite moieties, the photovoltaic performance of PSCs is largely limited by defects within the polycrystalline perovskites and the sensitivity to moisture. In this perspective, we focus on the chemically tailored interface materials to passivate the defects and improve the moisture stability of PSCs. First, we provide a brief overview of various molecular interface modifiers. Thereafter we provide examples from our recent work on organic ammonium halide‐based passivation materials as representatives to illustrate the design strategies and the modification effects. In the end, we shed light on the future development of organic ammonium halides for applications in PSCs. Abstract : Organic ammonium halides are effective molecular surface modifiers for perovskite solar cells (PSCs) to improve their power conversion efficiency and operational stability. Representative aliphatic and aromatic organic ammonium halides are reviewed per functionalities, and designing rationales have been discussed, shedding the light for potential wider application of organic ammonium halides in high performance PSCs.